1988
DOI: 10.1007/bf01773896
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium ions in the activation of rabbit psoas muscle

Abstract: This study tested the effects of free Ca++ on both the small-amplitude mechanical behaviour (dynamic stiffness and phase between 1 and 500 Hz) and the large-scale filament-sliding behaviour (Vmax) of single fibres of chemically-activated glycerol-extracted rabbit psoas muscle. Small-amplitude vibrations (0.1% peak-to-peak of initial length L0) were used to elicit fw, the frequency for maximum oscillatory work-production per cycle. The unloaded contraction velocity Vmax was measured during the same contractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
4
11
0
Order By: Relevance
“…Moss, 1986) and other laboratories (e.g. Farrow et al 1988). As reported previously, slack-test plots obtained at submaximal concentrations of Ca 2+ were biphasic (see control data in Fig.…”
Section: Tension and Velocity In Control Fibressupporting
confidence: 78%
See 1 more Smart Citation
“…Moss, 1986) and other laboratories (e.g. Farrow et al 1988). As reported previously, slack-test plots obtained at submaximal concentrations of Ca 2+ were biphasic (see control data in Fig.…”
Section: Tension and Velocity In Control Fibressupporting
confidence: 78%
“…
In mammalian skinned muscle fibres, several investigators have found that unloaded shortening velocity (V o ) decreases when Ca 2+ concentration is reduced to levels that induce submaximal isometric tensions (Julian, 1971;Julian et al 1986;Moss, 1986;Farrow et al 1988;Martyn et al 1994;Metzger, 1996). At saturating [Ca 2+ ], V o is maximal and invariant throughout the time course of shortening.
…”
mentioning
confidence: 99%
“…As it is seen, the dip frequency for skeletal or cardiac muscle is at least three orders of magnitude higher than what we obtained for the taenia coli. Since a negative phase in the spectrum indicates that the cross-bridges are generating energy and negative phase reaches maximum around the dip frequency, this frequency is considered to be related to the cross-bridge cycle [9,28,32]. It is well-known that smooth muscles have lower V max [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…This method is also used to find the differences in the contraction mechanisms of fast and slow muscles [8,18,22]. In skeletal and cardiac muscles, the frequency responses are obtained by changing the length of the muscle in the form of sinusoidal function [8][9][10][23][24][25][26] or pseudo-random binary noise (PRBN) [27][28][29]. Since analysis by means of the sine waves takes longer time, Brozovich and his colleagues developed a length perturbation sequence that consisted of multiple sine waves with increasing frequency and they applied this length perturbation to smooth muscle [16,18].…”
Section: Discussionmentioning
confidence: 99%
“…When a muscle is shortening at Vmax, the proportions of cross-bridges with strains greater than 1.0 and those with cross-bridge strains less than 1.0 would be equal, and external force developed by the muscle would be zero. More recent work (Moss 1986;Farrow et al 1988) clearly shows that [Ca 2+] has a profound effect on Vmax and also provides an explanation for the earlier discrepancies. At levels of Ca 2+ that were saturating with respect to isometric tension, shortening velocity is high and is constant during the period of shortening (Fig.…”
Section: Effects Of[ca 2+] On Shortening Velocitymentioning
confidence: 98%